Carbon Pseudocubes from Iron Oxide Templates for Capacitive Energy Storage - Sinan, Neriman; Ünür Yılmaz, Ece (Electrochemical Soc Inc, 2020)
A surface-protected etching approach was used to synthesize monodisperse partially hollow carbon nanostructures with pseudocubic shapes. Monodisperse chemical templates (alpha-Fe2O3, MF) were synthesized by the gel-sol method and coated with a polyvinylpyrrolidone (PVP) protective layer. Pyrrole monomers were dispersed around the PVP-protected alpha-Fe2O3 templates. Upon acidic etching, Fe3+ ions were released to initiate in situpolymerization of pyrrole to form Fe2O3@PPy (MFP) core-shell intermediates. The MFP particles were calcined to obtain partially hollow 3D pseudocubic carbon nanoparticles (PCC). The PCC delivered a high specific capacitance (395 F g(-1) at 0.2 A g(-1)) and enhanced cycling stability (5000 cycles at 4 A g(-1)). The superior electrochemical properties of the PCC is attributed to its cubic and partially hollow structure, which increases electric double layer capacitance by increasing charge storage surface, facilitates effective ion diffusion by reducing interparticle distances, and buffers volumetric changes associated with ion insertion through void space/pores. The simple and highly reproducible method presented in this work can be extended to produce various hollow or yolk-shell nanostructures as high-performance supercapacitor electrode materials. (C) 2020 The Electrochemical Society ("ECS"). Published on behalf of ECS by IOP Publishing Limited.
Keywords: Fe2O3; polypyrrole; pseudocubic carbon; self-template; Supercapacitors